1968
DOI: 10.1115/1.3597545
|View full text |Cite
|
Sign up to set email alerts
|

Transient Film Boiling of Water on a Horizontal Wire

Abstract: This paper reports an experimental and analytical investigation of transient film boiling of water from a horizontal submerged platinum wire following a large step change in wire temperature. Experimental vapor growth rate data were obtained from high-speed motion pictures with pool temperatures very close to saturation and wire temperatures ranging from 1245 to 1739 deg F. An analytical solution for vapor growth rate which assumes the primary mode of heat transfer within the vapor to be conduction is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In a transient film boiling study, McLean et al (137) found a delay time of 20 to 256 ^sec before film boiling was established while pulse heating a fine wire. A similar result, using a step power input, was seen by Pitts et al (163,164). Both Cole (50) and Hall and Harrison (86) found that subcooling retarded the formation of film boiling during transient heating.…”
Section: Sources Of Film Boiling Datasupporting
confidence: 75%
See 2 more Smart Citations
“…In a transient film boiling study, McLean et al (137) found a delay time of 20 to 256 ^sec before film boiling was established while pulse heating a fine wire. A similar result, using a step power input, was seen by Pitts et al (163,164). Both Cole (50) and Hall and Harrison (86) found that subcooling retarded the formation of film boiling during transient heating.…”
Section: Sources Of Film Boiling Datasupporting
confidence: 75%
“…This expression gave values in good agreement with their exact numerical solution. A somewhat similar analysis for transient film boiling from a horizontal wire has been presented by Pitts et al (163,164). The influence of sinusoidal pressure fluctuations on film boiling has been calculated analytically by Burmeister and Schoenhals (40,41).…”
Section: Film Boiling Models and Correlationsmentioning
confidence: 69%
See 1 more Smart Citation